Enhancing the usability of a task analysis method: A notation and environment for requirements... - Ormerod TC; Richardson J (Ergonomics)
This paper presents a notation and computer-based tool for the Sub-Goal Template (SGT) method, a task-analytic approach to specifying information requirements. In particular, it focuses upon the ergonomic redesign of a notation used in the SGT method for specifying contingent sequences in operators' tasks. Two experiments are reported in which two notations for redescribing sequences that involve making a choice between task alternatives are compared: a disjunctive form (Either ... or ...)-used in the original SGT scheme, and a conditional form with a redundant negative (If ... then ... if not ...), which has been promoted as a notation for capturing procedural sequences in computer programming. In experiment 1, performance with the conditional notation was better than with the disjunctive notation for redescribing simple and moderately complex task plans, although there was no difference for the most complex task plans. In experiment 2, a computer environment for specifying task plans using the SGT method was compared with a paper-based equivalent. In general, the computer environment was found to be easier to use and led to greater accuracy in plan redescription, although it was slower perhaps as a result of the constraints that it placed on participants. This paper argues for the necessity of ergonomic design in developing notations and tools to support task analysis methods.